Liquid membranes : principles and applications in chemical separations and wastewater treatment - Kislik, Vladimir S. (Elsevier, 2010)
This product provides comprehensive information on liquid membrane separations presenting the principles and applications of a variety of liquid membrane separation processes. A critical analysis of new technologies and their theoretical background is presented, as well as directions for future development.
Keywords: Membrane separation.; Sewage -- Purification -- Reverse osmosis process.; Liquid membranes.; elektronické knihy; electronic books